Learning Media in Writing Descriptive Texts: Bibliometric Analysis - Zuber; Nurfajrin Ningsih, Dini; Saepuloh, Asep; Ramadhani, Siva Malika Putri; Nuraeni, Intan; Adawiyah, Sulistia Nursyamsiyah (PT. Impola Toba Lendt, 2025)
Although research on learning to write descriptive texts continues to grow, there are still few studies that systematically map the trends and directions of research related to the use of learning media. Therefore, this study aims to analyze scientific developments on the use of media in learning to write descriptive texts using a bibliometric analysis approach. Data were obtained from 200 scientific articles published on Google Scholar during the period 2020–2024, collected using the Publish or Perish application, and analyzed through VOS viewer based on quantity, quality, and structural indicators. The results of the analysis show eight main clusters of research topics, namely descriptive text writing skills, types of media, learning models, digital technology, and visual approaches to writing. The research trend has increased since 2020, with Padlet, Instagram, and serial images being the dominant media studied. However, after 2023, no new prominent trends have been found. Density analysis shows that the topics of